Remote Sensing in Archaeology
XV, 554 p. 129 illus.
Keywords: Whether deployed in space or on the surface of the earth, remote sensing instruments are increasingly becoming standard archaeological tools. Space age techniques have begun to accumulate a wealth of information and unusual evidence such as the presence of sand-buried courses of ancient rivers in the Sahara and the associated remains of human occupations. Perhaps as important, some have been able to gather priceless knowledge without disturbing fragile sites—a capability that is particularly significant in this era of conservation. Remote Sensing in Archaeology illustrates the uses of advanced technology in archaeological investigation. It deals with hand-held instruments that probe the subsurface of the earth to unveil layering and associated sites; underwater exploration and photography of submerged sites and artifacts; and the utilization of imaging from aircraft and spacecraft to reveal the regional setting of archaeological sites and to assist in cultural resource management. In each case, the technical developments are explained first, followed by examples of applications as case studies. Contributors are renowned experts from the international scientific community. Each chapter is composed as a self-standing contribution with a summary and an introduction to help the reader grasp the value of its contents. The book is profusely illustrated with graphs and photographs to explain the methodologies and results, so that the reader may better understand the principles involved and apply the knowledge gained to similar environments. Complete lists of references cited will also allow the reader to investigate more deeply the problems and findings. "This book provides an excellent and diverse overview of the emerging capability of remote sensing archaeology and is a very valuable and important text for archaeologists in their quest to use advanced technology to help in their studies of exploration, and for remotesensing technologists and scientists by giving them a good understanding of the challenges that archaeologists find in their endeavors. The editors are to be applauded for bringing together such an excellent collection of authors and articles to cover this important emerging field." —Charles Elachi, Director, Jet Propulsion Laboratory (NASA), Pasadena, California.